Development of a droplet digital PCR assay for quantification of the proviral load of bovine leukemia virus - De Brun, María L. (2022)
Droplet digital PCR (ddPCR) is a highly sensitive tool developed for the detection and quantification of short-sequence variants—a tool that offers unparalleled precision enabling measurement of smaller-fold changes. We describe here the use of ddPCR for the detection of Bovine leukemia virus (BLV) DNA provirus. Serum samples and whole blood from experimentally infected sheep and naturally infected cattle were analyzed through ddPCR to detect the BLV gp51 gene, and then compared with serologic and molecular tests. The ddPCR assay was significantly more accurate and sensitive than AGID, ELISA, nested PCR, and quantitative PCR. The limit of detection of ddPCR was 3.3 copies/µL, detecting positive experimentally infected sheep beginning at 6 d post-infection. The ddPCR methodology offers a promising tool for evaluating the BLV proviral load, particularly for the detection of low viral loads.